Core text of neuroanatomy - Carpenter, Malcolm B. (Baltimore : Williams & Wilkins, 1991)
Uniformed Services University of the Health Sciences, Bethesda, Maryland. Concise, synoptic textbook for medical students. DNLM: 1. Nervous System - anatomy and histology.
Includes bibliographical references and index.
Keywords: Neuroanatomy; Nervous System -- anatomy & histology